L’incoronazione di spine (Mc 15,16-20a). Tortura fisica, subita da Gesù, o piuttosto la derisione della Sua dignità regale? - Grochowski, Zbigniew (The Biblical Annals, 2016)
The Passion Narrative constitutes the “heart” of all the Gospels. The attention of Christians who feed their faith on the Word of God usually concentrates on the physical suffering of Jesus. But the purpose of the Gospels seems to be different: cf. the lack of description of significant, long-lasting and cruel scenes, such as the “flagellation” and the “crucifixion” of Christ in Mc 15:15 and 15:24 (these episodes are “depicted” by one simple word: fragellw,saj and staurou /sin). That is why the pericope Mc 15:16-20a should be considered not (only) as the “Coronation of Thorns,” as it commonly is, but as a “Derision of Christ’s Royal Dignity”, as the context of the singular “act of thorns” suggests. In fact, aside from dressing Jesus in purple and beating his head with the reed, which indeed could cause physical suffering of the Savior (here we think of Jesus flogged and crowned by thorns), other elements of scorning (a mocking “saluting” of Jesus, spitting on him and the scoffing prostration of soldiers) had not touched Jesus’ body at all! As a consequence, these acts were surely not the source of his physical pain. Also, the crown itself did not necessarily have to cause Christ such huge suffering as is usually imagined. The pericope Mc 15:16-20a portrays the “Derision of Christ’s Royal Dignity” and, speaking of Jesus as the King, inscribes itself in the theme of “The Reign of God” in the Gospel of Mark.